Memahami Economic complexity Index (ECI) Bagian I ECI Sebagai Indeks Pembangunan Ekonomi Berbasis Produk - Roni Nababan (Jurnal Administrasi Bisnis, 2013)
Economic system consists of 3 elements which are divided into subject, object andinstitution which organized both. One method that can be used to measure effectiv-ity and performance of this economic system is by utilising economic developmentindex. Among them, can be found, indices based on subject and institution ap-proach. Meanwhile, one of the product based indices developed by The Centre forInternational Development (CID) Harvard University in 2010 is called EconomicComplexity Index (ECI). This index utilises network theory analysing 2 types ofconectivity; first, the concept of complexity and ubiquity which is the linkage be-tween a country and its products. Second, the concept of product proximity whichis the linkage among products itself. This article is trying to provide an introductoryreview about economic complexity index.Keywords: industrial policy, development index, private sector development,export expansion, international trading, national capabilities, inovation and science